Evaluation of the functionality of the virtual platform in the teaching process: analysis based on the usability factor - Omar Chamorro-Atalaya; Dora Arce-Santillan; Guillermo Morales-Romero; Beatriz Caycho-Salas; Teresa Guía-Altamirano; César León-Velarde; Risley Rengifo-Tello (Indonesian Journal of Electrical Engineering and Computer Science, 2023)
The use of virtual platforms has been increasing exponentially during the context of distance education, however, there are still limitations to innovate in pedagogical proposals. This can hinder the assurance of student learning, either due to the little planning that occurred in its incorporation, the little knowledge of teachers and students in the educational use or the lack of use of the functionalities that they have incorporated for communication. The purpose of the research is to evaluate the operability of the virtual platform in the teaching-learning process through analysis based on the usability factor, the results will allow us to continue improving the tools linked to distance higher education. At the development of the investigation, a reliability value of 0.985 was obtained by means of Cronbach's Alpha. It was found as findings that 73.8% perceive an improvement in communication and in the exchange of information. Regarding the usability factor, 73.9% fully agree with the information available on the virtual platform and its accessibility. From what was determined, it is concluded that 65.98% of students consider that the functionality of the virtual platform with respect to the usability factor positively influences the teaching-learning process.